The Effects of Gender Diversity, Age Diversity, and Organizational Structure on Sustainability Performance - Hakim, Rio Christantio; Agustina, Lidya (Universitas Pamulang, 2026)
This study examines the effect of board gender diversity, board age diversity, and organizational structure on corporate sustainability performance in Indonesia. Although companies included in the ESG Leaders Index are expected to demonstrate superior sustainability practices, empirical evidence reveals significant variation in ESG scores, indicating that membership in the index does not automatically guarantee consistent sustainability performance. This study adopts a quantitative approach by analyzing secondary data from 74 companies listed in the ESG Leaders Index of the Indonesia Stock Exchange during the 2022–2023 period. Multiple linear regression analysis is employed to test the proposed hypotheses, with sustainability performance measured using ESG scores provided by Refinitiv. The results show that board gender diversity and board age diversity do not have a significant effect on sustainability performance, indicating that demographic diversity alone is insufficient to influence ESG outcomes without the support of effective governance mechanisms. In contrast, organizational structure is found to have a positive and significant impact on sustainability performance. This study underscores the important role of organizational structure in strengthening ESG performance within the context of emerging economies and provides practical implications for firms and regulators. From a practical perspective, firms and regulators should prioritize strengthening governance structures rather than relying solely on symbolic board diversity. Future research is encouraged to incorporate broader diversity attributes and longer observation periods to enhance generalizability.